2020
DOI: 10.1038/s41598-020-70732-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes of central noradrenaline transporter availability in immunotherapy-naïve multiple sclerosis patients

Abstract: The neurotransmitter noradrenaline (NA) mediates arousal, attention and mood, and exerts antiinflammatory and neuroprotective effects. Alterations of monoamine signalling were reported in multiple sclerosis (MS) and psychiatric illness and may account for the high prevalence of comorbid depression and fatigue in MS patients. We assessed central noradrenaline transporter (NAT) availability using positron emission tomography (PET) and the NAT selective radiotracer S,S-[ 11 c] O-methylreboxetine in immunotherapy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Constrained independent component analysis (ICA). (A) Images depict PET atlases for dopamine, serotonin and norepinephrine transporters (colour bar represents normalised image intensity for the ligand binding potential) 14 15 44. (B) Images show the main resting state (RS) functional connectivity (FC) within components obtained by constrained ICA (effects of interest from SPM V.12 ANOVA models, age, sex and scanner adjusted, p<0.05 family-wise error corrected, colour bar reports F contrast values).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Constrained independent component analysis (ICA). (A) Images depict PET atlases for dopamine, serotonin and norepinephrine transporters (colour bar represents normalised image intensity for the ligand binding potential) 14 15 44. (B) Images show the main resting state (RS) functional connectivity (FC) within components obtained by constrained ICA (effects of interest from SPM V.12 ANOVA models, age, sex and scanner adjusted, p<0.05 family-wise error corrected, colour bar reports F contrast values).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence for direct damage in monoaminergic neurons in MS is hitherto scarce. A single pathological study outlined direct injury to locus coeruleus in eight MS specimens,29 whereas previous PET analyses showed increased noradrenergic transporter expression in the striatum and limbic cortex,14 decreased serotonin transporter expression in the hippocampus and increased serotonin transporter expression in the prefrontal cortex15 in patients with MS. Besides these direct observations, abnormalities of monoaminergic networks were also explored through diffusion or RS fMRI approaches demonstrating more widespread pathological abnormalities, resulting in fronto-limbic-striatum disconnection for the three monoaminergic networks 16–18 30.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study has shown higher NET expression in subcortical brain regions such as thalamus and amygdala in patients with MS. Changes in monoamine signaling reported in MS may contribute to the high prevalence of comorbid depression and fatigue in MS patients. 109 Since the noradrenergic system is significantly involved in neuropsychiatric disorders, targeting NET may be a promising approach to link neuroinflammation with neuropsychiatric symptoms in MS, such as cognitive impairment (Table 4).…”
Section: Monoamine Neurotransmitters/alkaloid Neurotransmittersmentioning
confidence: 99%